Osteomyelitis of the Rib in a Child With Indolent Symptoms - Archana Balamohan MD; Robert F. Buchmann DO (SAGE Publishing, 2022)
We describe a case of osteomyelitis of the rib caused by methicillin-susceptible Staphylococcus aureus . The patient presented with a subtle, indolent course leading to a suspected 2-year delay in diagnosis. This case highlights that the diagnosis of rib osteomyelitis, which can readily mimic other diagnoses, such as costochondritis, intraabdominal infections, pneumonia, or malignancies warrants a high index of suspicion. Albeit rare, pediatricians should be aware of the possibility of rib osteomyelitis in healthy children to help ensure a prompt diagnosis and appropriate, timely management.